Keterampilan literasi informasi pustakawan Universitas Negeri Malang dalam implementasi layanan berbasis inklusi sosial - Inawati Inawati; Setiawan Setiawan; Adi Prasetyawan (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. Inclusion-based libraries aim to improve information literacy, quality of life, and community welfare, as well as become a place for lifelong learning. The librarians need to have sufficient information literacy skills in implementing social inclusion-based services. Data Collection Methods. Qualitative case study approach was used. The data was collected by interviews, observations, and documentation from librarians at the Malang State University Library. Data Analysis. We analyzed our data by using data reduction, data presentation, and conclusion. Results and Discussion. Information literacy skills of librarians were examined by several indicators such as identify, scope, plan, gather, evaluate, manage, and present. Those indicators have not been applied, particularly to the implementation of social inclusion-based services. Five indicators of information literacy skills can be applied properly including identification of needs information, determining the scope of information needs, planning information retrieval strategies, gathering information sources, as well as evaluating. In this study, skills in managing and presenting information have not been implemented properly. Conclusion. The information literacy skills of librarians in social inclusion-based services have not been maximized due to absence of competency development, lack of librarians, and absence of collections and facilities that support all information needs based on the user.